The impact of Chinese volume-based procurement on pharmaceutical market concentration - Yang, Ying; Liu, Yuxin; Mao, Zongfu; Mao, Jing; Jin, Yalei (Frontiers in Pharmacology, 2024)
Objectives Optimizing the pharmaceutical industrial structure is the key mission of China’s healthcare reform. From the industrial structure perspective, this study empirically evaluated the impact of China’s national volume-based procurement (NVBP) policy on market concentration in the hospital-end drug market. Methods This study used drug procurement data of China’s public medical institutions which obtained from the national database. A quasi-natural experiment was designed involving eleven pairs of matched treatment-control region combinations, with NVBP policy as the intervention measure. The market was defined by drug name (molecular boundary) and city/province (geographical boundary). Market changes were measured from three dimensions: the number of enterprises and products, market share, and Herfindahl-Hirschman index (HHI). Dual comparison approach and difference-in-difference (DID) method with fixed effect model were applied to quantify policy impacts. Results The number of enterprises and products decreased by 18 and 83 in pilot regions after NVBP policy, far more than the decreases in control regions (6 and 21). The accumulative market share of 15 bid-winning enterprises increased by 53.67% in volume and 18.79% in value, among which the increment of enterprises with low baseline market share was more prominent (66.64% and 36.40%). Among three enterprise types, the market share of generic consistency evaluation (GCE) certificated generics significantly increased, GCE uncertificated generics significantly decreased, and originators slightly decreased. DID models indicated significantly positive impact of NVBP policy on market concentration, with HHI-volume and HHI-value increasing by 49.33% (β = 0.401, p < 0.01) and 21.05% (β = 0.191, p < 0.01). Conclusion The implementation of NVBP promoted the intensive drug circulation and supply of Chinese public hospitals, intensifying the exit of GCE uncertificated generics from the hospital-end market. NVBP combined with GCE standards significantly improved market concentration, which brought a positive signal of pharmaceutical industrial structure optimization in China. In the future context of normalized and institutionalized NVBP, the balance should be further sought between low drug prices and reliable hospital drug supply, sustainable industry development.